Spotlight on faculty member: Associate Professor Rossi Setiadji, environmental chemist - M. M., Yusoff; Saifful Kamaluddin, Muzakir; Nurul Nadia, Abd Razak; Muhammad Najib, Muhammad Nor (Penerbit UMP, 2009)
Dr. Rossi Setiodji, 49 years old, was born in Indonesia. He received hiS tertiary education training in Bogor as well as in the USA at the New Mexico State University in Los Cruces.